2011
DOI: 10.1007/s00726-011-0962-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism underlying the antioxidant activity of taurine: prevention of mitochondrial oxidant production

Abstract: An important function of the β-amino acid, taurine, is the regulation of oxidative stress. However, taurine is neither a classical scavenger nor a regulator of the antioxidative defenses, leaving uncertain the mechanism underlying the antioxidant activity of taurine. In the present study, the taurine antagonist and taurine transport inhibitor, β-alanine, was used to examine the mechanism underlying the antioxidant activity of taurine. Exposure of isolated cardiomyocytes to medium containing β-alanine for a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
270
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 375 publications
(285 citation statements)
references
References 24 publications
14
270
1
Order By: Relevance
“…Elevated concentrations of taurine are required in the mitochondria where its pH buffering capacity maintains optimum enzyme activity [44]. Taurine is also present in mitochondrial tRNA and thus is important for protein synthesis [44,45]. Taurine deficiency can result in mitochondrial oxidative stress in vitro [45], and rotifer-fed cod larvae have abnormal mitochondria in liver and intestinal cells (Elin Kjørsvik, personal communication).…”
Section: A Rotifer Diet Disrupts Glutathione Homeostasis and Redox Pomentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated concentrations of taurine are required in the mitochondria where its pH buffering capacity maintains optimum enzyme activity [44]. Taurine is also present in mitochondrial tRNA and thus is important for protein synthesis [44,45]. Taurine deficiency can result in mitochondrial oxidative stress in vitro [45], and rotifer-fed cod larvae have abnormal mitochondria in liver and intestinal cells (Elin Kjørsvik, personal communication).…”
Section: A Rotifer Diet Disrupts Glutathione Homeostasis and Redox Pomentioning
confidence: 99%
“…Taurine is also present in mitochondrial tRNA and thus is important for protein synthesis [44,45]. Taurine deficiency can result in mitochondrial oxidative stress in vitro [45], and rotifer-fed cod larvae have abnormal mitochondria in liver and intestinal cells (Elin Kjørsvik, personal communication). We found that many genes important for maintaining the mitochondrial redox environment -nrf2, gpx1, sod2, prdx3, prdx5 and msrb2 [19,46,47] -were differentially regulated in rotifer-fed larvae.…”
Section: A Rotifer Diet Disrupts Glutathione Homeostasis and Redox Pomentioning
confidence: 99%
“…Biochemically, this enhances the binding of the UUG codon to the taurine-modified AAU anticodon of tRNA Leu(UUR) , facilitating UUG decoding. When the formation of 5-taurinomethyluridine-tRNA Leu(UUR) is abolished, the biosynthesis of certain mitochondria encoded proteins dramatically declines, respiratory function falls, ATP generation decreases and the generation of oxidants by the respiratory chain increases (Jong et al 2012;Schaffer et al 2013). Another important function of taurine is the detoxification of xenobiotics and the neutralization of toxic aldehydes (Miyazaki and Matsuzaki 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major biochemical abnormalities of the tRNA Leu(UUR) mutations is decreased formation of 5-taurinomethyluridine in the wobble position of tRNALeu(UUR) (Kirino et al 2005;Kurata et al 2008). Because taurine conjugation enhances the interaction of the UUG codon with the taurine-modified AAU anticodon of tRNA Leu(UUR) , the synthesis of mitochondria encoded proteins, such as ND6, is highly dependent upon the 5-taurinomethyluridine modification (Jong et al 2012). Hence, taurine deficiency and MELAS are both associated with complex I deficiency (Santa 2010;Jong et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation